The Energy Crisis - McCracken, Paul W.; Hansen, Clifford P.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1974)
This is a published AEI (American Enterprise Institute) round table dialogue amongst committee members on energy crisis.
"An AEI Round Table held on 25, 26, and 27 September 1973 at the American Enterprise Institute for Public Policy Research, Washington, D.C."
ne 20/04/2018
Loan
Keywords: Energy Policy